Characteristics of Pepsin-Solubilised Collagen from the Skin of Splendid Squid (Loligo formosana) - Phanat Kittiphattanabawon; Sitthipong Nalinanon; Soottawat Benjakul; Hideki Kishimura (Journal of Chemistry)
Pepsin-solubilised collagen from the skin of splendid squid (SC) was isolated, partially purified by salt precipitation and dialysis prior to characterisation. The yield of SC was 75.3% (dry weight basis). SC with high purity was obtained as shown by the distinct UV absorption peak at 232 nm and high hydroxyproline content. Total sugar content of SC was 4.70% (dry weight basis), which was higher than that of collagen from calf skin (CC) (1.45% dry weight basis) (P<0.05). Based on SDS-PAGE and elution profile, SC might contain the mixed types of collagen (type SQ-I and type SQ-II), in which α- and β-chains were the major components. SC was rich in glycine and had high content of imino acids (189 residues/1000 residues). The degradation induced by chymotrypsin and lysyl endopeptidase was more pronounced in CC, compared with SC. The maximum transition temperature (Tmax) of SC was 34.1°C, which was about 7°C lower than that of CC. Fourier transform infrared spectra revealed that the triple-helical structure of SC was predominant with the copresence of carbohydrate moieties. Therefore, the skin of splendid squid, a byproduct from squid processing, can be an alternative source for collagen production.